Spatiotemporal analysis of malaria cases in the primary cluster in Purworejo District, Central Java Province - Febriansyah; Ahmad, Riris Andono; Fuad, Anis (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to describe the spatiotemporal distribution of indigenous malaria cases and to understand the transmission risk factors in the primary cluster of Purworejo District from January 2017 to June 2018. Methods: A Survey was conducted to observe the spatial clustering of indigenous malaria cases. The primary cluster was then associated with risk factors, including environmental, socioeconomic, and human factors, in the Purworejo District from January 2017 to June 2018. Results: A total of 538 cases were found, there were 303 cases of P. falciparum (15 of them gametocytes) and 235 cases of P. vivax. In space-time permutation analysis, there were five primary clusters formed with a radius ranging from 0.58 to 7.07 km, in which there were 316 cases in 72 hamlets. The majority of cases in the primary cluster exhibited the same pattern of exposure to weather conditions in the Purworejo District. In addition, the majority of cases were suffered by farmers (31.96%), students (28.16%), and housewives (17.09%). The case strengthens local transmission found in toddlers (4.11%) in all clusters, and more cases occur in the productive age (61.39%). Conclusion: There was spatial-temporal clustering of malaria cases, reinforced by the visualization of local transmission risk factors. Further intervention is necessary, particularly in high-risk areas.